2019
DOI: 10.1370/afm.2353
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Implementation Science Theory to Empower Primary Care Practices

Abstract: Observers of the past 10 to 15 years have witnessed the simultaneous growth of dramatic changes in the practice of primary care and the emergence of a new field of dissemination and implementation science (D&I). Most current implementation science research in primary care assumes practices are not meeting externally derived standards and need external support to meet these demands. After a decade of initiatives, many stakeholders now question the return on their investments. Overall improvements in quality met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Organizations may also want to consider building flexibility into ongoing telemedicine support plans. 29 As our study has shown, PCPs have had to adapt their practice approaches as well as their surroundings to make telemedicine work, and these findings should be considered as organizations continue to assess what adjustments are needed to support the ongoing use of telemedicine.…”
Section: Discussionmentioning
confidence: 92%
“…Organizations may also want to consider building flexibility into ongoing telemedicine support plans. 29 As our study has shown, PCPs have had to adapt their practice approaches as well as their surroundings to make telemedicine work, and these findings should be considered as organizations continue to assess what adjustments are needed to support the ongoing use of telemedicine.…”
Section: Discussionmentioning
confidence: 92%
“…Stakeholder engagement is an integral component of implementation [25,26]. Growing calls are being made for [27] and examples of embedded research models, such as practice-based research networks, learning health systems, and implementation laboratories [28], that foster collaborations between researchers, implementers, and policy-makers integrated within a healthcare system to conduct research.…”
Section: Establish and Maintain Community Stakeholder Engagement And mentioning
confidence: 99%
“…Further, an implementation framework can inform clarity. Stakeholders can be engaged in the application of an implementation framework by, for example, having them involved in defining the local health system needs and selecting EBP(s) and/ or implementation strategies in the EPIS implementation phase, as these are important to enhance their collaboration and ownership of the implementation effort [26].…”
Section: Establish and Maintain Community Stakeholder Engagement And mentioning
confidence: 99%
“…Fortunately, primary care scholars are generating new family medicine practice-based evidence across the implementation and dissemination research continuum. 9 Research on practice change draws explicitly on theory and measurement. Implementation science uses learning health systems and other real-world "collaboratories" 10 to "bake-in" external validity from the beginning.…”
mentioning
confidence: 99%